Results of comprehensive treatment of locally advanced oral cancer using regional intra-arterial chemotherapy - D. A. Safarov; M. A. Kropotov; I. V. Pogrebnyakov; S. B. Aliyeva (Опухоли головы и шеи)
Introduction. Head and neck cancers are a significant healthcare and social problem worldwide with an estimated 377,713 new cases and 177,757 deaths registered annually. The incidence of head and neck cancer in Russia is 4.12 per 100,000. Despite all the achievements of current oncology, approximately 50–60 % of patients with locally advanced head and neck cancer develop relapses within the first 2 years after treatment completion.The study objective is to analyze the effectiveness of regional intra-arterial polychemotherapy in the combined and comprehensive treatment of locally advanced oral cancer.Materials and methods. This prospective study included 29 patients with oral squamous cell carcinoma treated and followed-up at N.N. Blokhin National Cancer Research Center between 2017 and 2020. The majority of patients (82.8 %) had stage III–IV disease. We evaluated clinical response to neoadjuvant regional intra-arterial chemotherapy, pathomorphosis of the primary tumor after surgery, treatment toxicity, overall survival, and relapse-free survival.Results. The objective response rate assessed for the primary oral tumor after regional intra-arterial chemotherapy was 100 %; complete regression of the primary tumor was achieved in 82.8 % of patients. More than one-third of participants (35.5 %) had complete regression of metastases in regional lymph nodes. In 73.5 % of patients who had under gone neoadjuvant regional intra-arterial chemotherapy followed by surgery, we observed grade IV therapeutic pathomorphosis of the primary tumor. The 2-year relapse-free survival rate was 100 % in individuals with stage II–III disease and 92.9 ± 6.9 % in patients with stage IV disease.Conclusion. The administration of regional intra-arterial chemotherapy as an induction stage ensures high treatment efficacy and high rate of complete pathomorphological responses. This suggests the opportunity of conservative treatment for patients with locally advanced oral cancer, which is currently considered impossible for such patients. Moreover, this method demonstrated moderate systemic toxicity, which expands the indications for its use and increase treatment compliance.